DETERMINANTS OF NEET (NOT IN EMPLOYMENT, EDUCATION OR TRAINING) ON THE POLISH LABOUR MARKET - Rak, Anna M. (Management and Administration Journal, 2022)
The principal purpose of the study is to identify the individual risk factors of young people becoming the NEET generation on the Polish labour market. The first part of the paper comprises a literature-based overview of definitions of the NEET category based and a presentation of the risk factors of young people becoming NEET. The second part presents the results of empirical analyses conducted employing a questionnaire on a group of 120 individuals, aged 15 through 30, who met all criteria of the NEET definition set forth by the Employment Committee of the EU. The research demonstrates that among the major determinants of young people becoming NEET are financial hardship of their households, low motivation to continue formal education or change professional qualifications, and low level of job-seeking activity.